2021
DOI: 10.1002/ajmg.a.62100
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental disorder in an Egyptian family with a biallelic ALKBH8 variant

Abstract: Alkylated DNA repair protein AlkB homolog 8 (ALKBH8) is a member of the AlkB family of dioxygenases. ALKBH8 is a methyltransferase of the highly variable wobble nucleoside position in the anticodon loop of tRNA and thus plays a critical role in tRNA modification by preserving codon recognition and preventing errors in amino acid incorporation during translation. Moreover, its activity catalyzes uridine modifications that are proposed to be critical for accurate protein translation. Previously, two distinct hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Many of the CMG discoveries are still in the process of gathering cases, functional data, or going through the peer review publication process. 26 South Africa, Kenya, Egypt, 27,28 Iraq, 29 Chile 30,31 , Turkey, [32][33][34] and Lithuania. For some, this has involved training opportunities within a CMG-affiliated laboratory, while for others learning happened through collaborative meetings to discuss analysis results on teleconferences.…”
Section: Impact On the Rare Disease Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the CMG discoveries are still in the process of gathering cases, functional data, or going through the peer review publication process. 26 South Africa, Kenya, Egypt, 27,28 Iraq, 29 Chile 30,31 , Turkey, [32][33][34] and Lithuania. For some, this has involved training opportunities within a CMG-affiliated laboratory, while for others learning happened through collaborative meetings to discuss analysis results on teleconferences.…”
Section: Impact On the Rare Disease Communitymentioning
confidence: 99%
“…A special week-long Genomics course is incorporated into the medical school curriculum at Johns Hopkins and will be developed into an on-line training module. The CMGs have enabled researchers and clinicians investigating rare Mendelian diseases in the US and around the world to access gene discovery techniques, including those in countries where access to research opportunities is limited, such as the Democratic Republic of the Congo, 26 South Africa, Kenya, Egypt, 27, 28 Iraq, 29 Chile 30, 31 , Turkey, 3234 and Lithuania. For some, this has involved training opportunities within a CMG-affiliated laboratory, while for others learning happened through collaborative meetings to discuss analysis results on teleconferences.…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous loss-of-function variants in the ALKBH8 gene were first associated with syndromic ID ( Monies et al, 2019 ). Saad et al (2021) reported a novel ALKBH8 variant in an Egyptian family associated with a neurodevelopmental disorder. We report, to the best of our knowledge, on the fourth novel variant in ALKBH8 associated with syndromic ID.…”
Section: Discussionmentioning
confidence: 99%
“…Several signi cant genes in this study have been found to be associated with brain-related disorders. For instances, there is a close relationship between ALKBH8 and neurodevelopmental disorder including autosomal recessive nonsyndromic intellectual disability, and non-syndromic x-linked intellectual disability (30). Besides, INPP4A has a strong expression in the central nervous system and plays a vital role in the pathogenesis of intellectual disability, mental retardation syndrome and mental disorder (31).…”
Section: Discussionmentioning
confidence: 99%